Heat stroke leading to acute liver injury & failure: A case series from the Acute Liver Failure Study Group - Davis, Brian C.; Tillman, Holly; Chung, Raymond T.; Stravitz, Richard T.; Reddy, Rajender; Fontana, Robert J.; McGuire, Brendan; Davern, Timothy; Lee, William M. (Liver international, 2017)
Background & Aims In the United States, nearly 1000 annual cases of heat stroke are reported but the frequency and outcome of severe liver injury in such patients is not well described. The aim of this study was to describe cases of acute liver injury (ALI) or failure (ALF) caused by heat stroke in a large ALF registry. Methods Amongst 2675 consecutive subjects enrolled in a prospective observational cohort of patients with ALI or ALF between January 1998 and April 2015, there were eight subjects with heat stroke. Results Five patients had ALF and three had ALI. Seven patients developed acute kidney injury, all eight had lactic acidosis and rhabdomyolysis. Six patients underwent cooling treatments, three received N‐acetyl cysteine (NAC), three required mechanical ventilation, three required renal replacement therapy, two received vasopressors, one underwent liver transplantation, and two patients died—both within 48 hours of presentation. All cases occurred between May and August, mainly in healthy young men because of excessive exertion. Conclusions Management of ALI and ALF secondary to heat stroke should focus on cooling protocols and supportive care, with consideration of liver transplantation in refractory patients.